Recent Trends of Dosimetry in Radionuclide Therapy: Dosimetry Software - Shidahara, Miho (RADIOISOTOPES, 2025)
Internal dosimetry software for radionuclide therapy ranges from stand-alone conventional dose calculations to vendors-provided software that is installed in the workstation of nuclear medicine imaging system and seamlessly supports everything from image reconstruction to dose calculation based on therapeutic or alternative radionuclide imaging. This paper introduces the current state of internal dosimetry software in radionuclide therapy.